Sastra Perjalanan dan Patronase Politik Priayi Jawa: Pembacaan Semiotika Barthes dalam Cariyos Lelampahanipun Purwalelana - Rokhim, Mukhammad Nur; Zustiyantoro, Dhoni (University of Brawijaya, 2024)
The Javanese nobility, including regents and non-palace officials, had privileges to access certain colonial areas. In Cariyos Lelampahanipun Purwaelana, Purwaelana's journey through the residential areas of colonial officials and political offices, from Semarang to Batavia, implicitly depicts the lives of the priayi. Although implicit, this work reflects how the author, who received a Western-style education, also enjoyed the political safari facilities in various government offices. This article analyzes expressions that indicate Purwaelana's admiration and accessibility to symbols of political rights through Barthes' semiotic approach. The narratives and quotations reveal that Purwaelana managed to explore the elite residential areas and enter the Dutch colonial legal institutions. This admiration peaked when he visited Batavia and observed the splendour of the governor-general's palace. This experience contrasted with the restricted access experienced by Javanese kings and other regents under Dutch control.